Extracolonic cancer risk in Dutch patients with APC (adenomatous polyposis coli)-associated polyposis. Issue 1 (10th May 2017) - Ghorbanoghli, Zeinab; Bastiaansen, Barbara AJ; Langers, Alexandra MJ; Nagengast, Fokko M; Poley, Jan-Werner; Hardwick, James CH; Koornstra, Jan J; Sanduleanu, Silvia; de Vos tot Nederveen Cappel, Wouter H; Witteman, Ben JM; Morreau, H; Dekker, Evelien; et al.
Abstract : Background: Screening of patients with familial adenomatous polyposis (FAP) have led to a substantial reduction in mortality due to colorectal cancer (CRC). Recent guidelines suggest that surveillance of non-intestinal malignancies should also be considered in those patients. However, the value of these surveillance programmes is unknown. The aims of this study were (1) to assess the occurrence of extracolonic malignancies in a large series of adenomatous polyposis coli (APC) mutation carriers and (2) to evaluate the causes of death. Methods: All APC mutation carriers were selected from the Dutch polyposis registry. Data on causes of death were collected. Pathology reports were retrieved from the Dutch Pathology Registry. Results: A total of 85 extracolonic malignancies were diagnosed in 74 of 582 APC mutation carriers. Duodenal and skin cancers were the most prevalent cancers. Thyroid cancer was observed in only 1.5% of the cases. The main cause of death was cancer (59% of all deaths), with 42% due to CRC and 21% due to duodenal cancer. One patient died from thyroid cancer. The second and third most common causes of death were cardiovascular disease (13% of all deaths) and desmoid tumours (11% of all deaths), respectively. Conclusion: Extending surveillance programmes to other cancers will not contribute significantly to the survival of patients with FAP.